Double Mohand Integral Transform for Solving Wave Equations (Global Journal of Sciences, 2025)
Many fields of the physical sciences like physics, chemistry and mathematics use partial  differential equations to model a physical system. As a result, there are diverse techniques  in the literature for the solution of partial differential equations which tries to attain  symmetry. This paper proposes a fresh double transform method recognized as the double  Mohand Transform Method. Besides the explanation and major remarks of the proposed  double transform method, new results on partial derivatives are also given. Moreover, to  validate the importance of the double Mohand Transform Method in solving systems of  partial differential equations, a variety of symmetric examples on the wave equation with  various properties are solved using this approach.
Keywords: Double Mohand; transform method; Wave equation; partial differential; equations